Réglementation et certification des agrumes en Algérie - Assabah A. (Proceedings of the Mediterranean research network on certification of citrus (MNCC): 1998-2001, 2002)
In Algeria the certification programme for the sanitary improvement of citrus nursery productions is regulated by phytosanitary and phytotechnical rules; in particular, the administrative and technical procedures, the trueness-to-type and phytosanitary controls at each certification phase are presented.
5. and 6. meeting of the CIHEAM Mediterranean Research Network on Certification of Citrus (MNCC), 2000/10/04-06, Algiers (Algeria) and 2001/10-11/26-01, Cairo (Egypt)